2018
DOI: 10.1186/s12245-018-0205-8
|View full text |Cite
|
Sign up to set email alerts
|

Successful resuscitation for cardiac arrest due to severe accidental hypothermia accompanied by mandibular rigidity: a case of cold stiffening mimicking rigor mortis

Abstract: BackgroundIn cases of severe accidental hypothermia, it was recommended that resuscitation should be continued until the patient has rewarmed, as hypothermia itself can preserve cerebral function, and hypothermic cardiac arrest is reversible. During cardiopulmonary resuscitation for normothermic patients, muscle rigidity suggests the initiation of postmortem changes such as rigor mortis and can lead to the termination of resuscitation. Currently, the prognosis of cardiac arrest due to severe accidental hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Air pockets indicated that they had been breathing before HCA ( 66 , 94 , 95 , 100 ). Fifteen men and eight women suffered HCA secondary to drug or alcohol abuse ( 2 , 45 , 46 , 53 , 54 , 56 , 57 , 62 , 63 , 70 , 76 , 81 , 86 , 90 , 91 , 98 , 101 , 104 , 105 , 109 , 121 ). All underwent successful resuscitation with ECLS.…”
Section: Resultsmentioning
confidence: 99%
“…Air pockets indicated that they had been breathing before HCA ( 66 , 94 , 95 , 100 ). Fifteen men and eight women suffered HCA secondary to drug or alcohol abuse ( 2 , 45 , 46 , 53 , 54 , 56 , 57 , 62 , 63 , 70 , 76 , 81 , 86 , 90 , 91 , 98 , 101 , 104 , 105 , 109 , 121 ). All underwent successful resuscitation with ECLS.…”
Section: Resultsmentioning
confidence: 99%
“…Several findings can be confused with definitive signs of death, so that a living person could be declared dead or attempts could be made to resuscitate a deceased person. Mimics of dependent lividity include hematomas (a solid swelling of clotted blood within the tissues), reddish skin discoloration of parts of the body that are not generally the lowest parts in hypothermia and frostbite, and some skin conditions. Dependent lividity can be overlooked in poor lighting conditions, in people with dark skin, when there are superficial injuries, and when skin is covered with blood, dirt, or other substances (Figure 12). Mimics of postmortem rigidity include stiff joints in cold conditions, 5,69 severe hypothermia, sequelae of surgical procedures, or consequences of injuries. Conditions that can be confused with different stages of putrefaction include dark skin, hematomas, blistering, sepsis, and bleeding from the mouth and nose. Full thickness frostbite with black, mummified skin, especially affecting cold-exposed areas such as ears, nose, fingers, or toes can cause local mummification (dry gangrene), similar to beginning mummification after death (Figures 13A and B, Figures 14A and B). …”
Section: Discussionmentioning
confidence: 99%
“…As for the organ function damage,the myocardial damage was more serious after 1 hour immersion in low temperature seawater,but liver and kidney damage is less.These means that myocardial has poor tolerance to low temperature. When the core temperature drops, ventricular brillation is likely to occur, or even cardiac arrest [22] . What's more, due to the heart is an active blood supplier, low-temperature seawater immersion caused cardiac acceleration to ensure blood supply to vital organs throughout the body, thus increasing myocardial metabolism.But liver and kidney are a passive organ that receives blood,lowtemperature seawater would reduce the metabolic rate of liver and kidney function [23] .…”
Section: Discussionmentioning
confidence: 99%